2015
DOI: 10.1103/physrevc.91.044606
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional fission model with a complex absorbing potential

Abstract: We study the dynamics of multidimensional quantum tunneling by introducing a complex absorbing potential into a two-dimensional model for spontaneous fission. We first diagonalize the Hamiltonian with the complex potential to determine a resonance state as well as its lifetime. We then solve the time-dependent Schrodinger equation with such basis in order to investigate the tunneling path. We compare this method with the semiclassical method for multidimensional tunneling with imaginary time. A good agreement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Eventually, the number of particles in the fragments themselves should also be computed by projecting the full wave-function on good particle number. Each point of the frontier line would therefore be associated with a distribution of fragment mass and charges [21]. Taking into account this distribution would probably have the opposite effect of the projection on good particle number for the fissioning nucleus and should broaden the fission yields.…”
Section: Fission Fragment Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the number of particles in the fragments themselves should also be computed by projecting the full wave-function on good particle number. Each point of the frontier line would therefore be associated with a distribution of fragment mass and charges [21]. Taking into account this distribution would probably have the opposite effect of the projection on good particle number for the fissioning nucleus and should broaden the fission yields.…”
Section: Fission Fragment Distributionsmentioning
confidence: 99%
“…This approach automatically includes onebody dissipation effects: as the nucleus changes its shape, single-particle excitations (or quasi-particle excitations when pairing correlations are taken into account) are included, which slows the collective motion. TDDFT is probably the most promising approach to describe the structure of the fission fragments and various recent works have shown extremely encouraging results [19][20][21][22]. However, realistic simulation of a single fission event including full symmetry breaking and full treatment of pairing correlations is at the limit of what current supercomputers can handle [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the precedent study [21], we tested this method in a model case consisting of a schematic barrier. In the present study, we use a more realistic potential using the constrained Hartree-Fock+BCS theory.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have investigated this problem for the 40 Ca+ 96 Zr system [32]. By including the multi-neutron transfer process in the coupled-channels approach, we have found that the coupling strengths for the transfer couplings, which reproduce the transfer cross sections, largely underestimate fusion cross sections (see Fig.…”
Section: Interplay Between Fusion and Transfermentioning
confidence: 99%
“…3). To this end, we have included one octupole phonon excitation in 40 Ca, the octupole phonon excitations in 96 Zr up to the three-phonon levels, and the multi-nucleon transfer process up to three-neutron transfer, with both simultaneous and direct two-neutron transfer couplings [32]. We have assumed a transfer to a single effective channel for each transfer partition, and set its energy to be the same as the optimum Q-value, Q = 0.…”
Section: Interplay Between Fusion and Transfermentioning
confidence: 99%